Pentingnya Badan Intelijen Pertahanan dalam Non-Combat Military Mission: Instrumen Perhatian Khusus untuk Peningkatan Kapasitas dan Kapabilitas Pertahanan - Muhammad Arbani (Syntax Corporation Indonesia, 2024)
This research will focus on the importance of Defense Intelligence Agencies in Non-Combat Military Missions. This research method will use a qualitative approach with case studies to explore the importance of the Defense Intelligence Agency in Non-Combat Military Missions. The data will be collected through in-depth interviews with defense experts, intelligence analysts, and military personnel involved in non-combat missions, as well as through analysis of related documents and official reports. As a result, Military Intelligence has a vital role to play in defense policymaking by providing information to anticipate and confront potential threats, enabling comprehensive threat assessment, and supporting defense diplomacy with accurate intelligence. The establishment of the Defense Intelligence Agency under the Secretary of Defense was proposed because it could coordinate intelligence with military operations, speed up decision-making, and support non-combat missions with strategic intelligence. The agency also strengthens Indonesia's defense diplomacy by providing information for strategic planning and supporting collaboration with the local defense industry, which contributes to enhanced national defense capabilities and economic growth. To be effective, the intelligence function of the Defense Intelligence Agency must synergize with the existing intelligence community, to support Indonesia's mission to become an Asian Tiger.